Comparative bibliometric analysis of leading Open Access journals: a focus on Chinese and non-Chinese journals in science, technology, and medicine - Lei, Fang; Liang Du; Min Dong; Xuemei Liu (Malaysian Journal of Library and Information Science, 2023)
The objective of this study was to examine the scientific performance and internationalization of leading Chinese Open Access (OA) journals in the fields of science, technology, and medicine, specifically those published in English (referred to Chinese journals hereafter). Based on data taken from the Clarivate Analytics and Directory of Open Access Journals (DOAJ), a comparative bibliometric analysis was carried out. Fourteen Chinese journals were sampled, and a total of 22 non-Chinese OA journals were chosen for comparison. The analysis revealed that the majority of the journals were collaboratively published with large international publishers. While Chinese journals demonstrated a steady increase in publication productivity from 2018 to 2020, it remained noticeably lower than that of international journals. Additionally, Chinese journals received fewer citations from highly ranked journals, as evidenced by the three-fold higher Eigenfactor score observed in international journals compared to Chinese journals. Chinese journals exhibited a higher percentage of domestic manuscripts than international journals, as reflected in their elevated Index of National Orientation (INO) values. This study contributes to a better understanding of the scientific performance and internationalization of Chinese journals in the global publishing landscape, while also identifying potential areas for improvement.